Membangun Loyalitas Konsumen melalui Sosial Media Marketing Melalui Brand Image sebagai Pemediasi di E-Commerce - Simatupang, Selvi Octapia; Hargyatni, Titin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of Social Media Marketing on Consumer Loyalty, with Brand Image as a mediating variable, among Management students at STIE STEKOM Kartasura. The research method used was quantitative with a descriptive-verification approach through the distribution of questionnaires to 66 respondents. The results of validity and reliability tests indicated that all instrument items were valid and reliable. Tests for normality, multicollinearity, and heteroscedasticity indicated that the regression model met the classical assumptions. The t-test results indicated that Social Media Marketing had a significant but weak effect on Consumer Loyalty (sig. = 0.035), while Brand Image had a significant and moderate effect on Consumer Loyalty (sig. = 0.025). The F-test indicated that both independent variables simultaneously had a significant effect on Consumer Loyalty (sig. = 0.001). The results of the coefficient of determination test indicated that the influence of Social Media Marketing and Brand Image on Consumer Loyalty was 24%. The Sobel test shows that brand image significantly mediates the effect of social media marketing on consumer loyalty (Z = 4.03; p < 0.05). Thus, brand image plays a significant role in strengthening the effect of social media marketing on student consumer loyalty, particularly on the TikTok Shop platform.